İstanbul çevresinin bazı Lathyrus L.türleri (L.undulatus Boiss.,L. sylvestris L.,L.ochrus (L) DC.) üzerinde sitotaksonomik araştırmalar - Güneş, Fatma (My University, 1993)
unknown
Keywords: BİYOLOJİ-BİTKİLER